MODERATING ROLE OF SHARIAH COMMITTEE QUALITY ON THE RELATIONSHIP BETWEEN AUDIT COMMITTEE AND MALAYSIAN TAKAFUL PERFORMANCE - Monther Eldaia; saddam ali shatnawi; mustafa Mohamad Hanefah; Ainulashikin Binti Marzuki (Jurnal Internasional Ekonomi Islam, 2020)
The moderating effect of Shariah Committee Quality (SCQ) on the relationship between Audit Committee (AC) characteristics and Malaysian Takaful performance remains a challenge that is yet to be resolved. Malaysia plays a leader role in Muslim countries in Islamic Finance especially in Takaful industry and Shariah committee roles and duties. AC characteristics have a significant effect on corporate financial performance. The fundamental AC role is to supervise the corporate’s financial reporting practice, review of financial reports, auditing practice, internal accounting controls, and risk management practices. AC characteristics plays a crucial role in the overall Malaysian Takaful companies which is supposed to enhance financial performance. Hence, SCQ as part of the internal governance structure and control body of the institution, thereby, ensure Shariah compliance in all transactions and activities, and enhancing the credibility of institutions in the eyes of its shareholders and customers. SCQ can potentially moderate the relationship between AC and Malaysian Takaful performance. As an important mechanism of Corporate Governance (CG), In addition, agency theory and stewardship theory were used to develop the hypotheses. Several results of the previous literature were found fraternized, and inconsistent regarding the SCQ effect on firm performance or its effect on AC characteristics in general context, while the literature on Malaysia context remain scarce. It is expected that this SCQ moderation may considerably improve corporate performance by determining the strength or weakness of the relationship between AC characteristics and firm performance. Therefore, this paper conceptualized that ‘SCQ’ moderates the relationship between AC Chairman Specialization, Shariah Background, AC Independence and Meeting frequency, and Malaysian Takaful performance.